2017
DOI: 10.1128/jcm.00649-17
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium Keratitis in Germany

Abstract: keratitis is a destructive eye infection that is difficult to treat and results in poor outcome. In tropical and subtropical areas, the infection is relatively common and associated with trauma or chronic eye diseases. However, in recent years, an increased incidence has been reported in temperate climate regions. At the German National Reference Center, we have observed a steady increase in case numbers since 2014. Here, we present the first German case series of eye infections with species. We identified iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
71
1
18

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 62 publications
10
71
1
18
Order By: Relevance
“…We acknowledge that our estimate is prone to bias as we lack a reliable denominator and practices of sending fungal isolates to the mycology reference laboratory might have changed over time. However, our observation is in keeping with a general increase of keratitis cases and reports of increasing fungal keratitis cases in other countries such as the USA, Denmark and Germany (Jurkunas et al, 2009;Nielsen et al, 2015;Walther et al, 2017). Furthermore, one previous study indicated that the incidence of fungal keratitis was very low before 2010 in the Netherlands (Cheng et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We acknowledge that our estimate is prone to bias as we lack a reliable denominator and practices of sending fungal isolates to the mycology reference laboratory might have changed over time. However, our observation is in keeping with a general increase of keratitis cases and reports of increasing fungal keratitis cases in other countries such as the USA, Denmark and Germany (Jurkunas et al, 2009;Nielsen et al, 2015;Walther et al, 2017). Furthermore, one previous study indicated that the incidence of fungal keratitis was very low before 2010 in the Netherlands (Cheng et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…As filamentous fungi cannot penetrate intact cornea, the most common route of infection is through (micro) trauma or disruptive ocular surface disease. Several epidemiological studies indicate that the frequency of Fusarium keratitis may be increasing (Cheng et al, 1999;Stapleton et al, 2008Stapleton et al, , 2012Jurkunas et al, 2009;Nielsen et al, 2015;Walther et al, 2017). Based on a perceived increase of ocular Fusarium isolates sent to the Dutch mycology reference laboratory (Center of Expertise in Mycology Radboudumc/CWZ, Nijmegen, the Netherlands) for identification and in vitro susceptibility testing, a national survey was initiated.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the incidence of Fusarium keratitis has been increasing over the years and 15‐25 annual cases were found in 2014 to 2016 19 . Similar trends are seen in Germany 45 . Thus, the estimated incidence of 8 may underestimate the current incidence of Fusarium keratitis.…”
Section: Discussionmentioning
confidence: 88%
“…Das klassische Keimspektrum KL-assoziierter Keratitiden umfasst in absteigender Häufigkeit [2,5,8,16] Zudem verfügen einige Bakterien und Pilze (z. B. Candida spp.)…”
Section: Kontaktlinsenassoziierte Keratitisunclassified